2020
DOI: 10.1038/s41467-020-18860-4
|View full text |Cite
|
Sign up to set email alerts
|

Jagged1-Notch1-deployed tumor perivascular niche promotes breast cancer stem cell phenotype through Zeb1

Abstract: Zinc finger E-box binding homeobox 1 (Zeb1) has been demonstrated to participate in the acquisition of the properties of cancer stem cells (CSCs). However, it is largely unknown how signals from the tumor microenvironment (TME) contribute to aberrant Zeb1 expression. Here, we show that Zeb1 depletion suppresses stemness, colonization and the phenotypic plasticity of breast cancer. Moreover, we demonstrate that, with direct cell-cell contact, TME-derived endothelial cells provide the Notch ligand Jagged1 (Jag1)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
50
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(55 citation statements)
references
References 54 publications
(79 reference statements)
2
50
0
Order By: Relevance
“…Previous study has shown Ang2-TEK signaling as a key regulator in lymphogenous metastasis ( Gengenbacher et al, 2020 ). VEGF-A as a downstream factor of Zeb1 enhances breast cancer cells’ aggressiveness through sustaining stemness ( Jiang et al, 2020 ). Indeed, the regulatory networks of epigenomics, angiogenesis, and stemness maintenance are intricate.…”
Section: Discussionmentioning
confidence: 99%
“…Previous study has shown Ang2-TEK signaling as a key regulator in lymphogenous metastasis ( Gengenbacher et al, 2020 ). VEGF-A as a downstream factor of Zeb1 enhances breast cancer cells’ aggressiveness through sustaining stemness ( Jiang et al, 2020 ). Indeed, the regulatory networks of epigenomics, angiogenesis, and stemness maintenance are intricate.…”
Section: Discussionmentioning
confidence: 99%
“…Notch signaling is often activated in cancer cells that show enhanced stem cell maintenance. Notch-positive CSCs have recently been shown to be preferentially associated with endothelial cells within the tumor tissue, which is likely to act as a perivascular stem cell niche in breast cancer [ 84 , 85 ]. It was shown that tight association of quiescent cancer cells with an effective stem cell niche can significantly contribute to tumor dormancy and protect CSCs from therapeutic interventions such as chemo- and radiotherapy [ 84 ].…”
Section: The Relevance Of Notch Mutations Amplification Pathwaysmentioning
confidence: 99%
“…It was shown that tight association of quiescent cancer cells with an effective stem cell niche can significantly contribute to tumor dormancy and protect CSCs from therapeutic interventions such as chemo- and radiotherapy [ 84 ]. A similar perivascular stem cell niche for the persistence of CSC has recently been characterized in detail, and found to be promoted by active Jagged-1-Notch-1 signaling [ 84 , 85 ]. The Notch-dependent response in these CSCs involves the upregulation of ZEB1 in a positive feedback loop and stimulates endothelial cells by paracrine production of VEGFA.…”
Section: The Relevance Of Notch Mutations Amplification Pathwaysmentioning
confidence: 99%
See 2 more Smart Citations